Primary Neural Degeneration in the Human Cochlea: Evidence for Hidden Hearing Loss in the Aging Ear - Wu, P.Z.; Liberman, L.D.; Bennett, K.; de Gruttola, V.; O'Malley, J.T.; Liberman, M.C. (Neuroscience, 2019)
•Hair-cell and auditory-nerve loss were quantified in 20 “normal” humans 0–86 yrs.•Age-related loss of nerve fibers exceeded the rate of hair cell loss by almost 3:1.•In 10/16 ears over 50 yrs, >50% of auditory-nerve connections had degenerated.•This neural degeneration degrades hearing ability without affecting the audiogram. The noise-induced and age-related loss of synaptic connections between auditory-nerve fibers and cochlear hair cells is well-established from histopathology in several mammalian species; however, its prevalence in humans, as inferred from electrophysiological measures, remains controversial. Here we look for cochlear neuropathy in a temporal-bone study of “normal-aging” humans, using autopsy material from 20 subjects aged 0–89 yrs, with no history of otologic disease. Cochleas were immunostained to allow accurate quantification of surviving hair cells in the organ Corti and peripheral axons of auditory-nerve fibers. Mean loss of outer hair cells was 30–40% throughout the audiometric frequency range (0.25–8.0 kHz) in subjects over 60 yrs, with even greater losses at both apical (low-frequency) and basal (high-frequency) ends. In contrast, mean inner hair cell loss across audiometric frequencies was rarely >15%, at any age. Neural loss greatly exceeded inner hair cell loss, with 7/11 subjects over 60 yrs showing >60% loss of peripheral axons re the youngest subjects, and with the age-related slope of axonal loss outstripping the age-related loss of inner hair cells by almost 3:1. The results suggest that a large number of auditory neurons in the aging ear are disconnected from their hair cell targets. This primary neural degeneration would not affect the audiogram, but likely contributes to age-related hearing impairment, especially in noisy environments. Thus, therapies designed to regrow peripheral axons could provide clinically meaningful improvement in the aged ear.